Abstracts of poster presentations at the 2021 virtual annual of the Canadian Society for Pharmaceutical Sciences. - Kristine Warman (Frontiers Media S.A., 2021)
In 2021, the Canadian Society for Pharmaceutical Sciences (CSPS) partnered with he Pharmaceutical Society of Japan (PSJ) and the Canadian Chapter of Controlled Release Society (CC-CRS) and presented its annual matting in virtual style. Keynote speakers included Professor Michael Houghton - 2020 Nobel Laureate, Director of Li Ka Shing Applied Virology Institute (LKSAVI), Professor, Department of Medical Microbiology & Immunology, University of Alberta and Professor Yoshiharu Matsuura, Director, Center for Infectious Diseases Education and Research (CIDER), Osaka University, Japan.